If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -19 = 3(7 + 3n) + 8(8n + -5) -19 = (7 * 3 + 3n * 3) + 8(8n + -5) -19 = (21 + 9n) + 8(8n + -5) Reorder the terms: -19 = 21 + 9n + 8(-5 + 8n) -19 = 21 + 9n + (-5 * 8 + 8n * 8) -19 = 21 + 9n + (-40 + 64n) Reorder the terms: -19 = 21 + -40 + 9n + 64n Combine like terms: 21 + -40 = -19 -19 = -19 + 9n + 64n Combine like terms: 9n + 64n = 73n -19 = -19 + 73n Add '19' to each side of the equation. -19 + 19 = -19 + 19 + 73n Combine like terms: -19 + 19 = 0 0 = -19 + 19 + 73n Combine like terms: -19 + 19 = 0 0 = 0 + 73n 0 = 73n Solving 0 = 73n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-73n' to each side of the equation. 0 + -73n = 73n + -73n Remove the zero: -73n = 73n + -73n Combine like terms: 73n + -73n = 0 -73n = 0 Divide each side by '-73'. n = 0 Simplifying n = 0
| 180=111-u | | -12+19/-7= | | -12+-42/-7= | | 60x^2-20x+1=0 | | 84=2w+2L-3 | | 15y-11y=20 | | -12+-126/-7= | | x^2+(x*y)=120 | | 84+3x=1x | | -9u-5+6=19 | | -12+h/7=6 | | -a+5+6a=1+5a+3 | | -12+h/7= | | 8x+4(2-3x)=36-6x | | (4x-3)+3(3x+6)=5x-1 | | 4x^3-33x^2-30x=0 | | 2x+17+3x-4=180 | | 32=2x+14 | | 0.625=-0.50x | | 88+1.5h=94+2h | | 85=3(x-1)+8x | | -5(k-1)-(-6k+1)=9 | | 7a^2+49a+60=0 | | (sin(x))*2=116 | | 1x+-7=2x+-6 | | (sin(x))2=116 | | 4x^3-33x-30x=0 | | -3(2y-2)-y=-2(y-2) | | 4v-(6v+8)=8v-38 | | 88+1.5h=94-2h | | 9(3x+12x)= | | (x+3.3)m=28 |